2018
DOI: 10.3390/md16100393
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Metabolic Diversity in Marine Sponges Extracts by Controlling Extraction Parameters

Abstract: Metabolomics has become an important tool in the search for bioactive compounds from natural sources, with the recent inclusion of marine organisms. Of the several steps performed in metabolomics studies, the extraction process is a crucial step—one which has been overlooked for a long time. In the presented study, a pressurized liquid extraction system was used to investigate the effect of extraction parameters such as pressure, temperature, number of cycles, and solvent polarity on the chemical diversity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…through the mevalonic pathway [116][117][118][119]. Two more diastereomeric acetates of pelseneeriol-1 and -2 ( Figure 4) were further In sea hares, the Sri Lankan species Aplysia oculifera, possesses compounds obtained from the red algae Laurencia, such as srilankenyne (14) (Figure 3), while the digestive gland of Indic and West Pacific specimens presents brominated acetylenes instead [92,93]. Aplysia argus from Bahamas presents, among other compounds, the sesquiterpene ethers dactyloxene-B (15) ( Figure 3) and dihydroxydeodactol monoacetate in whole body extracts [94][95][96][97][98][99].…”
Section: Monocyclic Sesquiterpenoidsmentioning
confidence: 98%
“…through the mevalonic pathway [116][117][118][119]. Two more diastereomeric acetates of pelseneeriol-1 and -2 ( Figure 4) were further In sea hares, the Sri Lankan species Aplysia oculifera, possesses compounds obtained from the red algae Laurencia, such as srilankenyne (14) (Figure 3), while the digestive gland of Indic and West Pacific specimens presents brominated acetylenes instead [92,93]. Aplysia argus from Bahamas presents, among other compounds, the sesquiterpene ethers dactyloxene-B (15) ( Figure 3) and dihydroxydeodactol monoacetate in whole body extracts [94][95][96][97][98][99].…”
Section: Monocyclic Sesquiterpenoidsmentioning
confidence: 98%
“…1 showed bioactivity against most test pathogens compared to one DCM : ME crude extracts, which showed activity against C. albicans . Bayona et al [ 30 ] reported that the extraction of bioactive metabolites from marine sponges depends on several factors such as pH, pressure, polarity index, and extraction technique(s) used. Therefore, it cannot be concluded that DCM : ME is a weak extraction solvent for marine bioactive metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…samples and the presence of alkaloids and saponins in their ethanolic crude extracts. Several reasons could have led to different phytochemicals being extracted, such as the type of solvent used for extraction, extraction method, and the sponge species' environmental conditions under evaluation [ 30 ]. Therefore, ethanol as an extraction solvent results in the successful extraction of alkaloids and saponins in Clathria sp., while ethyl acetate results in flavonoids' isolation.…”
Section: Resultsmentioning
confidence: 99%
“…A study was conducted on the marine sponge Xestospongia sp. (Laubenfels, 1932) by Bayona et al (2018) looking at the correlation between the parameter pressure, temperature and solvent polarity and the diversity in the extracted compounds [53]. It was found that the solvent polarity and temperature applied during the extraction process are the most important factors influencing the metabolic diversity in the extract.…”
Section: Factors Affecting the Extractionmentioning
confidence: 99%
“…Various methods can be applied to obtain the crude extract [ 52 ]. The crude extract is known to be composed of a complex mixture of various metabolites, including alkaloids, terpenoids, peptides and quinones [ 53 , 54 ]. The extraction process can be divided into two categories, which are the traditional extraction method and newly emerging technologies based on the energy or mechanism [ 52 ].…”
Section: Chemistry Of Compounds From Marine Spongesmentioning
confidence: 99%